Fitness and performance classified according to body mass index and waist circumference for Canadian Forces personnel aged 50--59 years - Flanagan, Sarah (University of Ottawa (Canada), 2008)
Purpose. Examine the relationship between body mass index (BMI), Waist Circumference (WC), performance in the Canadian Forces (CF) EXPRES test, and the Five Common Tasks (5CT) fitness test for CF members 50-59 years. Hypothesis. Increasing BMI and WC are related to lower performance in the EXPRES and 5CT. Results. For males (n=127, mean BMI=27.7 kg/m2(+/-3.4), mean WC=96.99 cm(+/-9.8 cm)), increasing BMI and WC correlated (p< 0.05) with poorer results on the Land Evacuation, Low High Crawl, Sandbag Carry, VO2max, Push-Ups and Sit-Ups. Performance was significantly worse for males with an "Obese" BMI than other groups and for those with a WC≥102 cm. The results for females (n=27, mean BMI=25.8 kg/m2(+/-3.6), mean WC=84.5 cm(+/-9.3 cm)) were inconclusive due to the sample size. Conclusion. For males, increasing BMI and WC were related to lower performance on some components of CF physical fitness testing. Additionally, the high percent of "Obese" individuals identifies and an alarming trend towards increased health risk.
Keywords: Health Sciences, Recreation.